2022
DOI: 10.1088/1748-9326/ac5a66
|View full text |Cite
|
Sign up to set email alerts
|

Earlier crop flowering caused by global warming alleviated by irrigation

Abstract: Ensuring that crops flower within an optimal window minimises long-term risk of abiotic stress exposure, improving prospects for attaining potential yield. Here we define the optimal flowering period (OFP) as the calendar time in which long-term risk of frost, water and heat stress are collectively minimal. Using the internationally-renowned farming systems model APSIM, we characterised effects of climate change and extreme climatic events on the OFPs of barley, durum wheat, canola, chickpeas, fababean and mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 72 publications
3
6
0
Order By: Relevance
“…Thus, irrigation mitigates the extent to which development is increased as the climate warms and consequently the longer crop growing cycle allows greater biomass production and seed set. This result is analogous to findings of Schauberger et al 76 , and Muleke et al 11 . Our study also found that yield reductions were higher in the low rainfall ('dry and hot') regions of Griffith (41%) and Kerang (39%, Figs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, irrigation mitigates the extent to which development is increased as the climate warms and consequently the longer crop growing cycle allows greater biomass production and seed set. This result is analogous to findings of Schauberger et al 76 , and Muleke et al 11 . Our study also found that yield reductions were higher in the low rainfall ('dry and hot') regions of Griffith (41%) and Kerang (39%, Figs.…”
Section: Discussionsupporting
confidence: 92%
“…The length of the optimal flowering window varied between crop genotypes under irrigation and rainfed conditions across sites (Tables 5, S1, S2, S3 and S4). Generally, irrigation extended the OFP window compared with dryland crops, particularly for the late winter genotypes, consistent with findings by Muleke et al11 . The latest OFP was at Hagley for irrigated late winter genotypes of canola (25 September), chickpea (4 October), spring barley (5 November) and durum wheat (12 November).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Past work on agronomic adaptation to climate change has primarily focused on field‐scale interventions such as changes to management and/or genotype/crop type combinations to improve yield (Ibrahim et al, 2019; Langworthy et al, 2018; Liu et al, 2021; Liu, Harrison, Hunt, et al, 2020) such as that aimed at closing yield gaps (Angella et al, 2016; Bryan et al, 2014; Liu et al, 2015, 2022; Muleke, Harrison, de Voil, et al, 2022; Pradhan et al, 2015). However, higher crop yields do not necessarily translate to higher crop profitability, because above a certain level of inputs, the rate of return from increased inputs diminishes (Ibrahim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%